Silicon nitride ceramic and preparation method thereof

By using acrylic acid and polyvinyl alcohol in a specific proportion as binder, the particle size interval of the silicon nitride ceramic powder particles is adjusted, and the poor performance problems caused by the combination of binders in the prior art are solved, and a silicon nitride ceramic with high strength, low dielectric and low thermal expansion coefficient is achieved.

CN119841651AActive Publication Date: 2025-04-18HANGZHOU DAHE NEW MATERIAL TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411910814.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-18
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

When polyvinyl alcohol and polyethylene glycol are used as the binder for silicon nitride ceramics in the prior art, the particle size intervals of the powder particles vary greatly, resulting in insufficient performance indicators of silicon nitride ceramics.

Method used

Acrylic acid and polyvinyl alcohol are used as binders, and by adjusting their mass ratio to 1:0.4-0.5, the particle size interval of the powder particles after spray granulation is adjusted, which significantly increases the loose density of green bodies, thereby increasing the strength of silicon nitride ceramics.

Benefits of technology

By optimizing the combination and proportion of the binder, the strength and density of silicon nitride ceramics are significantly improved, the dielectric loss and thermal expansion coefficient are reduced, and the characteristics of high strength, low dielectric and low thermal expansion coefficient are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841651A_ABST
    Figure CN119841651A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramics, and discloses a silicon nitride ceramic and a preparation method thereof, the ceramic comprises the following raw materials in parts by weight: 72-80 parts of silicon nitride, 4-12 parts of a sintering aid, 5-10 parts of a binder, 3-8 parts of a lubricant and 0.1-1.5 parts of a dispersant, the binder is acrylic acid and polyvinyl alcohol, and the mass ratio of acrylic acid to polyvinyl alcohol is 1: 0.4-0.5; acrylic acid and polyvinyl alcohol are adopted as a binder in the raw materials of the silicon nitride ceramic, the particle size interval of powder particles after spray granulation can be regulated and controlled at a specific proportion after the polyvinyl alcohol and the acrylic acid in the binder are combined, the loose compactness of a green body can be remarkably improved, and therefore the strength of the silicon nitride ceramic is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a silicon nitride ceramic and a preparation method thereof. Background Art

[0002] Silicon nitride ceramics have excellent properties such as high strength, high hardness, high heat shock resistance, high wear resistance, high toughness, and corrosion resistance. They are widely used in core technology fields such as mechanical engineering, aerospace, national defense and military industry, and semiconductors. At present, the method of applying silicon nitride ceramics to semiconductor devices in the prior art mainly adopts a mask method to form a layer of silicon nitride film on the surface of the semiconductor device, such as a method for manufacturing a silicon nitride film and a semiconductor device disclosed in publication number CN110120343B. Since the process conditions for preparing semiconductors are relatively harsh, the parts of semiconductor manufacturing equipment also need to meet higher performance indicators, and the performance of conventional substrates cannot meet the use requirements. Therefore, technicians in this field propose to make silicon nitride ceramics into the required semiconductor manufacturing equipment parts, but at present, when silicon nitride is made into large parts, the shape of the parts is simple and the relevant performance indicators are also low. Therefore, it is necessary to further optimize the process conditions of silicon nitride ceramics to achieve the development and application of high-strength, low-dielectric, low-thermal expansion coefficient, and complex-shaped silicon nitride ceramic samples.

[0003] At present, silicon nitride is made into parts mainly by ball milling silicon nitride, sintering aid, binder, dispersant and lubricant into slurry, then the slurry is made into powder, then the powder is pressed into green body, and then the green body is sintered into silicon nitride ceramic parts; the methods of making powder mainly include vacuum ball milling, rotary vibrating screen and double cone mixer, spray granulation, spray granulation is a more commonly used granulation method, such as a method for preparing silicon nitride ceramic granulation powder disclosed in publication number CN113999019B, which points out that polyvinyl alcohol is used as a binder with high viscosity, and polyethylene glycol is used to increase the deformation ability of polyvinyl alcohol, so that the shrinkage of droplets during spray drying is greater and the powder is more densely stacked, so that a higher packaging density can be obtained; and the present invention, after further research, found that the combination of polyvinyl alcohol and polyethylene glycol has a large difference in the particle size range of the powder when used, and the particle size range can significantly improve the bulk density of silicon nitride ceramics within a specific range, thereby improving the performance of silicon nitride ceramics. Therefore, choosing a suitable binder is of great significance to improving the performance of silicon nitride ceramics. Summary of the invention

[0004] The present invention aims at the problem that when polyvinyl alcohol and polyethylene glycol are used as binders for silicon nitride ceramics in the prior art, there is a large difference in particle size range. A silicon nitride ceramic and a preparation method thereof are provided. The binder in the silicon nitride ceramic raw material adopts acrylic acid and polyvinyl alcohol. The polyvinyl alcohol and acrylic acid in the binder are combined in a specific ratio to regulate the particle size range of the powder particles after spray granulation, and can significantly improve the loose density of the green body, thereby significantly improving the strength of the silicon nitride ceramic.

[0005] The specific technical scheme of the present invention is: A silicon nitride ceramic, the raw materials of which are measured in parts: 75-80 parts of silicon nitride, 5-12 parts of sintering agent, 5-10 parts of binder, 3 to 8 parts of lubricant, Dispersant 0.1-1.5 parts; The adhesive is acrylic acid and polyvinyl alcohol, and the mass ratio of acrylic acid to polyvinyl alcohol is 1:0.4-0.5.

[0006] The present invention provides a silicon nitride ceramic. The raw materials of the ceramic include silicon nitride, a sintering aid, a binder, a lubricant and a dispersant. The binder includes acrylic acid and polyvinyl alcohol in a specific ratio. The prior art points out that when polyvinyl alcohol is used as a binder, the powder particles prepared by spray drying of the slurry can shrink rapidly and quickly form spherical powder particles, thereby improving the loose density of the green body. However, the present invention finds that when polyvinyl alcohol is used as a binder, the extremely rapid shrinkage of the powder particles prepared by spray drying will lead to a larger difference in particle size distribution. The present invention finds through experiments that the difference in particle size distribution of the powder particles is not that the larger the better, but that a better loose density can be obtained within a specific range. Therefore, in view of the above problem, the present invention further optimizes the polyvinyl alcohol binder. After testing, it is found that when acrylic acid and polyvinyl alcohol with a mass ratio of 1:0.4 to 0.5 are used as a binder, the particle size range of the powder particles can be optimized, and the loose density of the green body is significantly improved within this particle size range.

[0007] Preferably, the sintering aids are aluminum oxide and yttrium oxide.

[0008] Preferably, the mass fraction of the aluminum oxide is 2 to 5 parts, and the mass fraction of the yttrium oxide is 3 to 7 parts.

[0009] Preferably, the particle size of the aluminum oxide is 0.5 to 0.9 μm, and the particle size of the yttrium oxide is 0.8 to 1.2 μm.

[0010] The sintering aid of the present invention uses aluminum oxide and yttrium oxide. Silicon nitride ceramics are mainly densified through the liquid phase during sintering. Therefore, during the pressureless sintering process, the sintering aids aluminum oxide and yttrium oxide react with silicon oxide on the surface of silicon nitride particles to generate a liquid phase. Under the action of capillaries, the silicon nitride particles rotate and rearrange to form a denser stacking state, and the liquid phase also fills more pores, so that the porosity of the silicon nitride ceramics is significantly reduced, the density is significantly increased, the bending strength is significantly increased, and the dielectric loss is significantly reduced.

[0011] Preferably, the lubricant includes one or more of stearic acid, lauric acid and fatty acid; and the dispersant is polyacrylamide.

[0012] The dispersant of the present invention selects polyacrylamide, and the commonly used dispersant is polyethylene glycol. At the same time, the prior art points out that when polyethylene glycol and polyvinyl alcohol are used together, the shrinkage of polyvinyl alcohol can be accelerated, so the selection of a suitable dispersant is also important. Therefore, after screening, the present invention finds that when polyacrylamide and a binder are used in combination, the classification difference of the particle size range of the powder particles can be further reduced, thereby further improving the loose density of the green body. At the same time, ammonium polyacrylate can be used as an anti-hydration agent to perform anti-hydration treatment on silicon nitride powder. Silicon nitride powder will undergo hydrolysis reaction when it meets water, and the silicon nitride powder after hydrolysis has serious agglomeration phenomenon. Ammonium polyacrylate can form an isolation layer between silicon nitride powder and water medium, and its addition can inhibit the hydrolysis reaction during high-speed ball milling.

[0013] A method for preparing the above-mentioned silicon nitride ceramic comprises the following steps: ball-milling silicon nitride, sintering aid, binder, surfactant, dispersant and water to prepare slurry, spray-granulating the slurry to prepare powder, charging the powder into a mold and cold isostatically pressing the powder to prepare a green body, and rough-machining, degreasing and sintering the green body to prepare silicon nitride ceramic.

[0014] Preferably, the moisture content of the powder is 0.3-0.8%, and the bulk density is 0.95-0.97 g / cm 3 .

[0015] Preferably, the cold isostatic pressing pressure is 120-160 MPa, the time is 1-5 min, and the density of the green body is 2.0-2.1 g / cm 3 .

[0016] Preferably, the degreasing temperature is 450-550° C., and the degreasing time is 5-8 hours.

[0017] Preferably, the sintering temperature is 1750-1780°C.

[0018] The present invention also provides a method for preparing the above-mentioned silicon nitride ceramics, which includes six steps of preparing slurry by ball milling, preparing powder particles by spray drying, preparing green bodies by cold isostatic pressing, preparing rough-machined parts by rough machining of the green bodies, degreasing the rough-machined parts to prepare degreasing rough products, and sintering the degreasing rough products to prepare silicon nitride ceramics. The method has a simple process and can be mass-produced. The silicon nitride ceramic parts produced have the characteristics of high strength, low dielectric constant, and low thermal expansion coefficient.

[0019] Compared with the prior art, this application has the following technical effects: (1) The binder of the present invention uses acrylic acid and polyvinyl alcohol in a specific ratio. The use of the binder can optimize the particle size range of the powder particles produced by spray drying, and the loose density of the green body is significantly improved within this particle size range; (2) When the dispersant polyacrylamide of the present invention is used in combination with the binder, the classification difference of the particle size range of the powder particles can be further reduced, and the loose density of the green body can be further improved; (3) The preparation method of the present invention comprises six steps of preparing slurry by ball milling, preparing powder by spray drying, preparing green body by cold isostatic pressing, preparing rough-processed components by rough processing of the green body, preparing degreased rough products by degreasing the rough-processed components, and preparing silicon nitride ceramics by sintering the degreased rough products. The method is simple in process and can be mass-produced. The silicon nitride ceramic parts produced have the characteristics of high strength, low dielectric constant and low thermal expansion coefficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The following are SEM images of the powder particles prepared by spray drying using the methods of Examples 1 to 3.

[0021] Figure 2 The SEM images of silicon nitride ceramics prepared in Examples 1 to 3 are shown.

[0022] Figure 3 Schematic diagram of silicon nitride ceramic parts made in Examples 1 to 3. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with the embodiments.

[0024] Embodiment 1: A method for preparing silicon nitride ceramics comprises the following steps: Step 1: Inject 76 parts of silicon nitride powder, 8 parts of sintering aid (3 parts of aluminum oxide powder and 5 parts of yttrium oxide powder), 1 part of dispersant (ammonium polyacrylate) and 60 parts of deionized water into a ball mill according to mass proportions, ball mill for 6 hours until the powder is evenly dispersed, then add 10 parts of adhesive (acrylic acid and polyvinyl alcohol in a mass ratio of 7:3) and 5 parts of lubricant (fatty acid) and continue ball milling for 1 hour to make a slurry; Step 2: Inject the slurry into the spray granulation device for spray granulation to form powder. The inlet temperature of the spray granulation device is 190°C, the outlet temperature is 90°C, the moisture content of the powder is 0.5%, and the bulk density is 0.966g / cm 3 ; Step 3: Put the powder into the molding mold, and then use 140Mpa pressure to perform cold isostatic pressing for 1 to 5 minutes to form a green body. The density of the green body is 2.07g / cm 3 ; Step 4: Grinding and rough-machining the outer shape of the green part to make a rough-machined part; Step 5: Place the rough-machined part in a degreasing furnace at 500°C for 3 hours, and then cool it naturally to room temperature to obtain a degreased rough product; Step six: Place the degreased crude product in the graphite mold of the vacuum sintering furnace, bury and compact the degreased crude product with buried powder, then slowly heat the sintering furnace to 1760℃ and keep it warm for 3 hours. Flow nitrogen in the furnace to maintain the pressure in the furnace at a slightly positive pressure. After the insulation is completed, cool it to room temperature with the furnace to make silicon nitride ceramics, and then finely process and clean the silicon nitride ceramics to make silicon nitride ceramic parts.

[0025] Embodiment 2: A method for preparing silicon nitride ceramics comprises the following steps: Step 1: Inject 76 parts of silicon nitride powder, 8 parts of sintering aid (3 parts of aluminum oxide powder and 5 parts of yttrium oxide powder), 1 part of dispersant (ammonium polyacrylate) and 60 parts of deionized water into a ball mill according to mass proportions, ball mill for 6 hours until the powder is evenly dispersed, then add 10 parts of adhesive (acrylic acid and polyvinyl alcohol in a mass ratio of 1:0.4) and 5 parts of lubricant (fatty acid) and continue ball milling for 1 hour to make a slurry; Step 2: Inject the slurry into the spray granulation device for spray granulation to form powder. The inlet temperature of the spray granulation device is 190°C, the outlet temperature is 90°C, the moisture content of the powder is 0.5%, and the bulk density is 0.958g / cm 3 Step 3: Put the powder into the molding mold, and then use 140Mpa pressure to perform cold isostatic pressing for 1 to 5 minutes to form a green body. The density of the green body is 2.06g / cm 3 ; Step 4: Grinding and rough-machining the outer shape of the green part to make a rough-machined part; Step 5: Place the rough-machined part in a degreasing furnace at 500°C for 3 hours, and then naturally cool it to room temperature to obtain a degreased rough product; Step six: Place the degreased crude product in the graphite mold of the vacuum sintering furnace, bury and compact the degreased crude product with buried powder, then slowly heat the sintering furnace to 1760℃ and keep it warm for 3 hours. Flow nitrogen in the furnace to maintain the pressure in the furnace at a slightly positive pressure. After the insulation is completed, cool it to room temperature with the furnace to make silicon nitride ceramics, and then finely process and clean the silicon nitride ceramics to make silicon nitride ceramic parts.

[0026] Embodiment 3: A method for preparing silicon nitride ceramics comprises the following steps: Step 1: Inject 76 parts of silicon nitride powder, 8 parts of sintering aid (3 parts of aluminum oxide powder and 5 parts of yttrium oxide powder), 1 part of dispersant (ammonium polyacrylate) and 60 parts of deionized water into a ball mill according to mass proportions, ball mill for 6 hours until the powder is evenly dispersed, then add 10 parts of adhesive (acrylic acid and polyvinyl alcohol in a mass ratio of 1:0.5) and 5 parts of lubricant (fatty acid) and continue ball milling for 1 hour to make a slurry; Step 2: Inject the slurry into the spray granulation device for spray granulation to form powder. The inlet temperature of the spray granulation device is 190°C, the outlet temperature is 90°C, the moisture content of the powder is 0.6%, and the bulk density is 0.954g / cm 3 Step 3: Put the powder into the molding mold, and then use 140Mpa pressure to perform cold isostatic pressing for 1 to 5 minutes to form a green body. The density of the green body is 2.05g / cm 3 ; Step 4: Grinding and rough-machining the outer shape of the green part to make a rough-machined part; Step 5: Place the rough-machined part in a degreasing furnace at 500°C for 3 hours, and then naturally cool it to room temperature to obtain a degreased rough product; Step six: Place the degreased crude product in the graphite mold of the vacuum sintering furnace, bury and compact the degreased crude product with buried powder, then slowly heat the sintering furnace to 1760℃ and keep it warm for 3 hours. Flow nitrogen in the furnace to maintain the pressure in the furnace at a slightly positive pressure. After the insulation is completed, cool it to room temperature with the furnace to make silicon nitride ceramics, and then finely process and clean the silicon nitride ceramics to make silicon nitride ceramic parts.

[0027] Embodiment 4: A method for preparing silicon nitride ceramics comprises the following steps: Step 1: Inject 72 parts of silicon nitride powder, 12 parts of sintering aid (3 parts of aluminum oxide powder and 5 parts of yttrium oxide powder), 1 part of dispersant (ammonium polyacrylate) and 60 parts of deionized water into a ball mill according to mass proportions, ball mill for 6 hours until the powder is evenly dispersed, then add 10 parts of adhesive (acrylic acid and polyvinyl alcohol in a mass ratio of 7:3) and 5 parts of lubricant (stearic acid) and continue ball milling for 1 hour to make a slurry; Step 2: Inject the slurry into the spray granulation device for spray granulation to form powder. The inlet temperature of the spray granulation device is 190°C, the outlet temperature is 90°C, the moisture content of the powder is 0.3%, and the bulk density is 0.96g / cm 3 ; Step 3: Put the powder into the molding mold, and then use 120Mpa pressure to perform cold isostatic pressing for 1 to 5 minutes to form a green body. The density of the green body is 1.98g / cm 3 ; Step 4: Grinding and rough-machining the outer shape of the green part to make a rough-machined part; Step 5: Place the rough-machined part in a degreasing furnace at 500°C for 3 hours, and then naturally cool it to room temperature to obtain a degreased rough product; Step six: Place the degreased crude product in the graphite mold of the vacuum sintering furnace, bury and compact the degreased crude product with buried powder, then slowly heat the sintering furnace to 1750℃ and keep it warm for 3 hours. Flow nitrogen in the furnace to maintain the pressure in the furnace at a slightly positive pressure. After the insulation is completed, cool it to room temperature with the furnace to make silicon nitride ceramics, and then finely process and clean the silicon nitride ceramics to make silicon nitride ceramic parts.

[0028] Embodiment 5: A method for preparing silicon nitride ceramics comprises the following steps: Step 1: Inject 80 parts of silicon nitride powder, 3 parts of sintering aid (1.5 parts of aluminum oxide powder and 2.5 parts of yttrium oxide powder), 1 part of dispersant (ammonium polyacrylate) and 60 parts of deionized water into a ball mill according to mass proportions, ball mill for 6 hours until the powder is evenly dispersed, then add 10 parts of adhesive (acrylic acid and polyvinyl alcohol in a mass ratio of 7:3) and 5 parts of lubricant (lauric acid) and continue ball milling for 1 hour to make a slurry; Step 2: Inject the slurry into the spray granulation device for spray granulation to form powder. The inlet temperature of the spray granulation device is 190°C, the outlet temperature is 90°C, the moisture content of the powder is 0.7%, and the bulk density is 0.96g / cm 3 ; Step 3: Put the powder into the molding mold, and then use 160Mpa pressure to perform cold isostatic pressing for 1 to 5 minutes to form a green body. The density of the green body is 2.0g / cm 3 ; Step 4: Grinding and rough-machining the outer shape of the green part to make a rough-machined part; Step 5: Place the rough-machined part in a degreasing furnace at 500°C for 3 hours, and then naturally cool it to room temperature to obtain a degreased rough product; Step six: Place the degreased crude product in the graphite mold of the vacuum sintering furnace, bury and compact the degreased crude product with buried powder, then slowly heat the sintering furnace to 1780℃ and keep it warm for 3 hours. Flow nitrogen in the furnace to maintain the pressure in the furnace at a slightly positive pressure. After the insulation is completed, cool it to room temperature with the furnace to make silicon nitride ceramics, and then finely process and clean the silicon nitride ceramics to make silicon nitride ceramic parts.

[0029] Comparative Example 1: Compared with Example 1, in Comparative Example 1, the binder is 10 parts of polyvinyl alcohol, and the steps are as follows: Step 1: Inject 76 parts of silicon nitride powder, 8 parts of sintering aid (3 parts of aluminum oxide powder and 5 parts of yttrium oxide powder), 1 part of dispersant (ammonium polyacrylate) and 60 parts of deionized water into a ball mill according to mass proportions, ball mill for 6 hours until the powder is evenly dispersed, then add 10 parts of adhesive (polyvinyl alcohol) and 5 parts of lubricant (fatty acid) and continue ball milling for 1 hour to make a slurry; Step 2: Inject the slurry into the spray granulation device for spray granulation to form powder. The inlet temperature of the spray granulation device is 190°C, the outlet temperature is 90°C, the moisture content of the powder is 0.5%, and the bulk density is 0.915g / cm 3 ; Step 3: Put the powder into the molding die, and then use 140Mpa pressure to perform cold isostatic pressing for 1 to 5 minutes to form a green body. The density of the green body is 1.91g / cm 3 ; Step 4: Grinding and rough-machining the outer shape of the green part to make a rough-machined part; Step 5: Place the rough-machined part in a degreasing furnace at 500°C for 3 hours, and then naturally cool it to room temperature to obtain a degreased rough product; Step six: Place the degreased crude product in the graphite mold of the vacuum sintering furnace, bury and compact the degreased crude product with buried powder, then slowly heat the sintering furnace to 1760℃ and keep it warm for 3 hours. Flow nitrogen in the furnace to maintain the pressure in the furnace at a slightly positive pressure. After the insulation is completed, cool it to room temperature with the furnace to make silicon nitride ceramics, and then finely process and clean the silicon nitride ceramics to make silicon nitride ceramic parts.

[0030] Comparative Example 2: Compared with Example 1, in Comparative Example 2, the binder is 10 parts of acrylic acid, and the steps are as follows: Step 1: Inject 76 parts of silicon nitride powder, 8 parts of sintering aid (3 parts of aluminum oxide powder and 5 parts of yttrium oxide powder), 1 part of dispersant (ammonium polyacrylate) and 60 parts of deionized water into a ball mill according to mass proportions, ball mill for 6 hours until the powder is evenly dispersed, then add 10 parts of adhesive (acrylic acid) and 5 parts of lubricant (fatty acid) and continue ball milling for 1 hour to make a slurry; Step 2: Inject the slurry into the spray granulation device for spray granulation to form powder. The inlet temperature of the spray granulation device is 190°C, the outlet temperature is 90°C, the moisture content of the powder is 0.6%, and the bulk density is 0.921g / cm 3 ; Step 3: Put the powder into the molding mold, and then use 140Mpa pressure to perform cold isostatic pressing for 1 to 5 minutes to form a green body. The density of the green body is 1.93g / cm 3 ; Step 4: Grinding and rough-machining the outer shape of the green part to make a rough-machined part; Step 5: Place the rough-machined part in a degreasing furnace at 500°C for 3 hours, and then naturally cool it to room temperature to obtain a degreased rough product; Step six: Place the degreased crude product in the graphite mold of the vacuum sintering furnace, bury and compact the degreased crude product with buried powder, then slowly heat the sintering furnace to 1760℃ and keep it warm for 3 hours. Flow nitrogen in the furnace to maintain the pressure in the furnace at a slightly positive pressure. After the insulation is completed, cool it to room temperature with the furnace to make silicon nitride ceramics, and then finely process and clean the silicon nitride ceramics to make silicon nitride ceramic parts.

[0031] Comparative Example 3: Compared with Example 1, the ratio of acrylic acid to polyvinyl alcohol in the binder in Comparative Example 3 is 1:1, and the steps are as follows: Step 1: Inject 76 parts of silicon nitride powder, 8 parts of sintering aid (3 parts of aluminum oxide powder and 5 parts of yttrium oxide powder), 1 part of dispersant (ammonium polyacrylate) and 60 parts of deionized water into a ball mill according to mass proportions, ball mill for 6 hours until the powder is evenly dispersed, then add 10 parts of adhesive (acrylic acid and polyvinyl alcohol in a mass ratio of 1:1) and 5 parts of lubricant (fatty acid) and continue ball milling for 1 hour to make a slurry; Step 2: Inject the slurry into the spray granulation device for spray granulation to form powder. The inlet temperature of the spray granulation device is 190°C, the outlet temperature is 90°C, the moisture content of the powder is 0.5%, and the bulk density is 0.937g / cm 3 ; Step 3: Put the powder into the molding mold, and then use 140Mpa pressure to perform cold isostatic pressing for 1 to 5 minutes to form a green body. The density of the green body is 2.01g / cm 3 ; Step 4: Grinding and rough-machining the outer shape of the green part to make a rough-machined part; Step 5: Place the rough-machined part in a degreasing furnace at 500°C for 3 hours, and then naturally cool it to room temperature to obtain a degreased rough product; Step six: Place the degreased crude product in the graphite mold of the vacuum sintering furnace, bury and compact the degreased crude product with buried powder, then slowly heat the sintering furnace to 1760℃ and keep it warm for 3 hours. Flow nitrogen in the furnace to maintain the pressure in the furnace at a slightly positive pressure. After the insulation is completed, cool it to room temperature with the furnace to make silicon nitride ceramics, and then finely process and clean the silicon nitride ceramics to make silicon nitride ceramic parts.

[0032] Comparative Example 4: Compared with Example 1, the ratio of acrylic acid to polyvinyl alcohol in the binder in Comparative Example 4 is 1:0.1, and the steps are as follows: Step 1: Inject 76 parts of silicon nitride powder, 8 parts of sintering aid (3 parts of aluminum oxide powder and 5 parts of yttrium oxide powder), 1 part of dispersant (ammonium polyacrylate) and 60 parts of deionized water into a ball mill according to the mass fraction, ball mill for 6 hours until the powder is evenly dispersed, then add 10 parts of adhesive (acrylic acid and polyvinyl alcohol in a mass ratio of 1:0.1) and 5 parts of lubricant (fatty acid) and continue ball milling for 1 hour to make a slurry; Step 2: Inject the slurry into the spray granulation device for spray granulation to form powder. The inlet temperature of the spray granulation device is 190°C, the outlet temperature is 90°C, the moisture content of the powder is 0.5%, and the bulk density is 0.936g / cm 3 ; Step 3: Put the powder into the molding mold, and then use 140Mpa pressure to perform cold isostatic pressing for 1 to 5 minutes to form a green body. The density of the green body is 2.02g / cm 3 ; Step 4: Grinding and rough-machining the outer shape of the green part to make a rough-machined part; Step 5: Place the rough-machined part in a degreasing furnace at 500°C for 3 hours, and then naturally cool it to room temperature to obtain a degreased rough product; Step six: Place the degreased crude product in the graphite mold of the vacuum sintering furnace, bury and compact the degreased crude product with buried powder, then slowly heat the sintering furnace to 1760℃ and keep it warm for 3 hours. Flow nitrogen in the furnace to maintain the pressure in the furnace at a slightly positive pressure. After the insulation is completed, cool it to room temperature with the furnace to make silicon nitride ceramics, and then finely process and clean the silicon nitride ceramics to make silicon nitride ceramic parts.

[0033] Comparative Example 5: Compared with Example 1, in Comparative Example 5, the dispersant is polyethylene glycol, and the steps are as follows: Step 1: Inject 76 parts of silicon nitride powder, 8 parts of sintering aid (3 parts of alumina powder and 5 parts of yttrium oxide powder), 1 part of dispersant (polyethylene glycol) and 60 parts of deionized water into a ball mill according to mass proportions, ball mill for 6 hours until the powder is evenly dispersed, then add 10 parts of adhesive (acrylic acid and polyvinyl alcohol in a mass ratio of 7:3) and 5 parts of lubricant (fatty acid) and continue ball milling for 1 hour to make a slurry; Step 2: Inject the slurry into the spray granulation device for spray granulation to form powder. The inlet temperature of the spray granulation device is 190°C, the outlet temperature is 90°C, the moisture content of the powder is 0.6%, and the bulk density is 0.929g / cm 3 ; Step 3: Put the powder into the molding mold, and then use 140Mpa pressure to perform cold isostatic pressing for 1 to 5 minutes to form a green body. The density of the green body is 2.0g / cm 3 ; Step 4: Grinding and rough-machining the outer shape of the green part to make a rough-machined part; Step 5: Place the rough-machined part in a degreasing furnace at 500°C for 3 hours, and then naturally cool it to room temperature to obtain a degreased rough product; Step six: Place the degreased crude product in the graphite mold of the vacuum sintering furnace, bury and compact the degreased crude product with buried powder, then slowly heat the sintering furnace to 1760℃ and keep it warm for 3 hours. Flow nitrogen in the furnace to maintain the pressure in the furnace at a slightly positive pressure. After the insulation is completed, cool it to room temperature with the furnace to make silicon nitride ceramics, and then finely process and clean the silicon nitride ceramics to make silicon nitride ceramic parts.

[0034] Comparative Example 6: Compared with Example 1, the defatted crude product in Comparative Example 7 was not buried with powder, and the other conditions were the same as those in Example 1.

[0035] Test example 1: The properties of the silicon nitride ceramics obtained in Examples 1 to 5 and Comparative Examples 1 to 6 were tested, and the test items included: density, bending strength, thermal expansion coefficient, dielectric constant and dielectric loss. The density of the sample is accurately determined using the Archimedes drainage method; The flexural strength was measured by the three-point bending method on a universal testing machine according to GB / T 6569-1986; The thermal expansion coefficient is measured using a thermal expansion instrument according to GB / T 16535-2008 standard; The dielectric constant and dielectric loss were tested by the Q meter method according to JIS C2141 standard, and the test frequency was 13.56MHz.

[0036] The test results are shown in Table 1.

[0037] Table 1 Properties of silicon nitride ceramics As shown in Table 1, the density of the silicon nitride ceramics prepared in Examples 1 to 3 is 3.17-3.19 g / cm 3 , bending strength can reach 750MPa, thermal expansion coefficient can reach 2.78×10 -6 / ℃, the dielectric constant can reach 9.17, and the dielectric loss can reach 5.19×10 -3 The above results show that the silicon nitride ceramics prepared by the present invention have the advantages of high strength, low dielectric loss and low thermal expansion coefficient.

[0038] Example 4 and Example 5 are silicon nitride ceramics made from different raw material ratios. The results show that the raw material ratio has an important influence on the performance of silicon nitride ceramics, so the raw material ratio can be adjusted according to the required performance requirements.

[0039] Comparative Example 1 is a silicon nitride ceramic made using only polyvinyl alcohol as a binder. Compared with Example 1, the strength of Comparative Example 1 is lower than that of Example 1, and the thermal expansion coefficient, dielectric constant and dielectric loss of Comparative Example 1 are all higher than those of Example 1; Comparative Example 2 is a silicon nitride ceramic made using only acrylic acid as a binder. Compared with Example 1, the strength of Comparative Example 2 is lower than that of Example 1, and the thermal expansion coefficient, dielectric constant and dielectric loss of Comparative Example 2 are all higher than those of Example 1; Comparative Examples 3 and 4 respectively adjust the ratio of acrylic acid to polyvinyl alcohol. After analyzing the results of Comparative Examples 3 and 4, it is found that the strength of the silicon nitride ceramic made when the ratio of acrylic acid to polyvinyl alcohol is not within a specific range is lower than that of Example 1, and the thermal expansion coefficient, dielectric constant and dielectric loss are also significantly higher than those of Example 1. From the above results, it can be seen that the silicon nitride ceramic made with acrylic acid and polyvinyl alcohol as a binder at a specific ratio has the characteristics of high strength, low dielectric constant and low expansion coefficient.

[0040] In Comparative Example 5, the dispersant is polyethylene glycol. The results show that the various properties of the silicon nitride ceramics obtained when polyethylene glycol is used as a dispersant are worse than those in Example 1. This indicates that when polyacrylamide is used in combination with a binder, it can optimize the particle grading, inhibit the hydrolysis of the powder, and improve the performance of the silicon nitride ceramics.

[0041] In Comparative Example 6, no embedding powder was used for embedding, so the sample could not be formed into porcelain.

[0042] Test example 2: The powder particle size range and green loose density obtained in Example 1 and Comparative Examples 1 to 5 were tested. The powder particle size and particle size range were tested by a laser particle size analyzer, and the loose density of the granulated powder was tested by a loose density meter. The test results are shown in Table 2.

[0043] Table 2. Spray granulation particle size distribution table of Example 1 and Comparative Examples 1 to 5 As shown in Table 2, it can be seen from the results of Example 1 and Comparative Examples 1 to 5 that the difference in binders has an important influence on the particle size distribution interval of the powders made by spray drying. Different binder selections and binder ratios obtain different powder particle size intervals. In addition, it can be seen from the results of the bulk density and particle size interval that the particle size interval is not the more uniform the distribution or the greater the distribution difference, the better, but the best bulk density will be obtained within a specific particle size interval. In addition to meeting the basic physical property requirements, the granulated powder also needs to meet the requirements of particle grading. The granulated powder with excellent particle grading has a higher bulk density, the formed green particles are densely packed, there are few pores after sintering, and the product has a high degree of densification. The present invention characterizes the particle grading by the percentage of the particle size distribution of each embodiment.

[0044] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A silicon nitride ceramic, characterized in that: The raw materials in measured parts include: Silicon nitride 72~80 parts, 4~12 parts of burning aid, 5~10 parts of binder, 3~8 parts of lubricant, Dispersant 0.1~1.5 parts; The adhesive is acrylic acid and polyvinyl alcohol, and the mass ratio of acrylic acid to polyvinyl alcohol is 1:0.4-0.

5.

2. The silicon nitride ceramic according to claim 1, characterized in that: The sintering aids are aluminum oxide and yttrium oxide.

3. The silicon nitride ceramic according to claim 2, characterized in that: The mass fraction of the aluminum oxide is 2 to 5 parts, and the mass fraction of the yttrium oxide is 3 to 7 parts.

4. The silicon nitride ceramic according to claim 2 or 3, characterized in that: The particle size of the aluminum oxide is 0.5-0.9 μm, and the particle size of the yttrium oxide is 0.8-1.2 μm.

5. The silicon nitride ceramic according to claim 1, characterized in that: The lubricant comprises one or more of stearic acid, lauric acid and fatty acid; the dispersant is polyacrylamide; and the adhesive is acrylic acid and polyvinyl alcohol.

6. A method for preparing the silicon nitride ceramic according to any one of claims 1 to 5, characterized in that: The following steps are involved: Silicon nitride, sintering aids, binders, surfactants, dispersants and water are ball-milled to form slurry, the slurry is spray-granulated to form powder, the powder is loaded into a mold and cold isostatically pressed to form a green body, and the green body is roughly processed, degreased and sintered to form silicon nitride ceramics.

7. The preparation method according to claim 6, characterized in that: The moisture content of the powder is 0.3-0.8%, and the bulk density is 0.95-0.97 g / cm 3 .

8. The preparation method according to claim 6, characterized in that: The cold isostatic pressing pressure is 120-160 MPa, the time is 1-5 min, and the density of the green body is 2.0-2.1 g / cm 3 .

9. The preparation method according to claim 6, characterized in that: The degreasing temperature is 450-550°C, and the degreasing time is 5-8 hours.

10. The preparation method according to claim 6, characterized in that: The sintering temperature is 1750-1780°C.

Citation Information

Patent Citations

  • Methods for manufacturing silicon nitride films and semiconductor devices

    CN110120343B

  • A method for preparing silicon nitride ceramic granulated powder

    CN113999019B

  • Preparation method of silicon nitride ceramics by water-base granulation and direct cold isostatic press moulding

    CN106083068A

  • Silicon nitride ceramic material and preparation method thereof

    CN107651965A

  • Silicon nitride ceramic prepared by using binder spray molding technology and method

    CN116655391A